Magnetic Order in Heisenberg Models on Non-Bravais Lattice: Popov-Fedotov Functional Method - Nga, Pham Thi Thanh; Thang, Nguyen Toan (Communications in Physics, 2019)
We study magnetic properties of ordered phase in Heisenberg model on a non-Bravais lattice by means of Popov - Fedotov trick, which takes into account a rigorous constraint of a single occupancy. We derive magnetization and free energy using sadle point approximation in the functional integral formalism. We illustrate the application of the Popov – Fedotov approach to the Heisenberg antiferromagnet on a honeycomb lattice.